Therapeutic potential of TRPM8 channels in cancer treatment - Ochoa, Sara V.; Casas, Zulma; Albarracín, Sonia L.; Sutachan, Jhon Jairo; Torres, Yolima P. (Frontiers in Pharmacology, 2023)
The transient receptor potential melastatin 8 (TRPM8) channel is a nonselective cation channel expressed in neuronal and non-neuronal tissues, where is involved in several processes including thermosensation, differentiation, and migration. TRPM8 channels also participate in physiological processes related to cancer as proliferation, survival, and invasion. Prostate cancer is the best-described cancer and these channels have an important role in diagnosis, prognosis, and treatment. In addition, it has been reported that TRPM8 channels are involved in the progress of pancreatic, breast, bladder, colon, gastric, and skin cancer as well as glioblastoma and neuroblastoma. Cancer is a multifactorial process associated with changes in signaling pathways leading to variations in cell cycle and gene expression. In this review, we summarize the current knowledge on the role of TRPM8 channels in cancer progression. We also include a discussion about the therapeutic potential of TRPM8 in carcinogenesis, which has been proposed as a cancer biomarker and molecular target for cancer therapy.